Evaluation of biological effects of water on the human body to change the energo-informational status = Оценка биологического влияния воды на организм человека по изменению его энерго-информационного состояния - Pesotskaya, L.; Glukhova, N.; Evdokimenko, N.; Zukow, W. (Journal of Education, Health and Sport, 2016)
Pesotskaya L., Glukhova N., Evdokimenko N., Zukow W. Evaluation of biological effects of water on the human body to change the energo-informational status = Оценка биологического влияния воды на организм человека по изменению его энерго-информационного состояния. Journal of Education, Health and Sport. 2016;6(9):736-756. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.159223 http://ojs.ukw.edu.pl/index.php/johs/article/view/3916 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 24.09.2016. <span style="font-size: 14.0pt; line-height: 107%; font-family: 'Times New Roman','serif'; mso-fareast-font-family: 'Times New Roman'; color: #333333; mso-ansi-language: EN-US; mso-fareast-language: RU;" lang="EN-US">EVALUATION OF BIOLOGICAL EFFECTS OF WATER ON THE HUMAN BODY TO CHANGE THE ENERGO-INFORMATIONAL STATUS <span style="font-size: 12.0pt; line-height: 107%; font-family: 'Times New Roman','serif'; mso-fareast-font-family: 'Times New Roman'; color: #333333; mso-ansi-language: EN-US; mso-fareast-language: RU;" lang="EN-US"> <span style="font-size: 14pt; line-height: 107%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">1<span style="font-size: 14pt; line-height: 107%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">Pesotskaya L., 2Glukhova N., 3<span style="font-size: 14pt; line-height: 107%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">Evdokimenko N., 4Zukow W. <span style="font-size: 12.0pt; line-height: 107%; font-family: 'Times New Roman','serif'; mso-fareast-font-family: 'Times New Roman'; color: #333333; mso-ansi-language: EN-US; mso-fareast-language: RU;" lang="EN-US"> 1Dnipropetrovsk medical Academy Ministry of Health of Ukraine,<span style="font-size: 12pt; line-height: 107%; font-family: 'Times New Roman', serif; color: #002060; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">pesotskaya23@mail.ru 2National mining University, Dnepropetrovsk, Ukraine, glnavi@ukr.net 3Ukrainian chemical-technological University, Dnepropetrovsk, Т<span style="font-family: 'Times New Roman', serif; color: #002060; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">anya@ibv.dp.ua <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; line-height: 12pt; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">4Faculty of Physical Education, Health and Tourism, Kazimierz Wielki University, Bydgoszcz, Poland w.zukow@ukw.edu.pl <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;"> <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;"> <p class="MsoNormal" style="margin-bottom: 0.0001pt; text-align: justify; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;"> <span style="font-size: 14pt; line-height: 115%; font-family: 'Times New Roman', serif; color: #333333; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">Abstract. <span style="font-size: 14pt; line-height: 115%; font-family: 'Times New Roman', serif; color: #333333; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">In the paper the results of the assessment of environmental parameters of two natural water samples on the basis of analyzing the characteristics of energy-the state of the human body, which was used as a detector. Conducted kirlianography fingers latching on x-ray film during the next time interval: immediately before and after the adoption of the water and through the week. The obtained images werescanned to determine the emission regions corresponding to organs and systems of the body in accordance with the scheme P. Mandela. Quantitatively assessed characteristics of the image brightness: the median relations of the minimum and maximum brightness values and their difference. The observed changes in energy activity and regulating the drainage systems of the body by drinking water, which confirms the informative value of kirlianography in the rapid assessment of biological activity of water. <span style="font-size: 14pt; line-height: 115%; font-family: 'Times New Roman', serif; color: #333333; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US"> <span style="font-size: 14pt; line-height: 115%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">Key words: kirlianography, digital image processing, natural water<span style="font-size: 10pt; line-height: 115%; font-family: Arial, sans-serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">. <span style="font-size: 10pt; line-height: 115%; font-family: Arial, sans-serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US"> ОЦЕНКА БИОЛОГИЧЕСКОГО ВЛИЯНИЯ ВОДЫ НА ОРГАНИЗМ ЧЕЛОВЕКА ПО ИЗМЕНЕНИЮ ЕГО ЭНЕРГО-ИНФОРМАЦИОННОГО СОСТОЯНИЯ 1Песоцкая Л.А., 2Глухова Н.В., 3Евдокименко Н.М., Zukow W. 1ГУ «Днепропетровская медицинская академия МОЗ Украины» 2ГВУЗ «Национальный горный университет» г. Днепропетровск, Украина 3ГВУЗ «Украинский химико-технологический университет», г. Днепропетровск, 4UKW w Bydgoszcz, Polska Аннотация. В работе получены оценки экологических параметров двух образцов природной воды на основе анализа характеристик энергоинформационного состояния организма человека, который использовался в качестве детектора. Проведена кирлианфотография пальцев рук с фиксацией на рентгеновской пленке в течение следующего временного интервала: непосредственно до и после принятия воды и через неделю. Полученные изображения сканировались с целью определения областей свечения, соответствующих органам и системам организма согласно схеме П. Мандела. Количественно оценивались характеристики яркости изображения: медиана отношения минимального и максимального значения яркости и их разность. Отмечены изменения энергетической активности дренажных и регулирующих систем организма при приеме воды, что подтверждает информативность кирлианфотографии при экспресс-оценке биологической активности воды. Ключевые слова: кирлианфотография, цифровая обработка изображений, природная вода. <span style="font-size: 10pt; line-height: 115%; font-family: Arial, sans-serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">